Comparative Analysis of Gojek and Grab Excellence Strategies in Improving the Market in Jember Regency - Moch Arief; Misbahul Munir; Hersa Farida Qoriani (Syntax Corporation Indonesia, 2023)
Kotler and Armstrong state that competitive advantage is an advantage gained by offering lower value or by providing greater benefits due to higher prices. Ironically, the importance of competitiveness has faded with decades of great expansion and prosperity, resulting in many companies losing sight of competitive advantage in the struggle to further develop in pursuit of diversification. Porter pointed out that there are several strategies that can be developed by companies such as increasing product differentiation, cheaper prices than competitors, good delivery systems, and easier payment systems as well as alternative strategies that can be developed, namely by increasing capital for business development, adding production equipment machinery, and training programs for employees. At this time Gojek and Grab are growing rapidly in running online transportation. Where Gojek and Grab dominate the market share in Indonesia, especially in Jember Regency. Of the many online transportation circulating on social media, Gojek and Grab are very widely used by consumers